2006
DOI: 10.1002/srin.200606405
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Potential Sources in Refractory Materials during Steel Casting

Abstract: It is well known that the presence of dissolved hydrogen in cast steel can cause defects that appear in hot rolling and forging of steel parts with heavy sections, and also contributes to the formation of internal cracks and blowholes during the solidification of the liquid steel. These problems are especially important in the continuous casting process. So, hydrogen levels must be kept at a minimum in this process. The aim of this work is to investigate possible sources of hydrogen, focusing on the materials … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…It was also found the possibility to reduce hydrogen pick-up with inertization. Bragança et al [7] did a work about this subject. The results of their research showed that not only the control of the humidity content in refractory materials is critical, but the phase transformations that the materials suffer during the casting process are important as well.…”
Section: Mathematical Modelmentioning
confidence: 99%
“…It was also found the possibility to reduce hydrogen pick-up with inertization. Bragança et al [7] did a work about this subject. The results of their research showed that not only the control of the humidity content in refractory materials is critical, but the phase transformations that the materials suffer during the casting process are important as well.…”
Section: Mathematical Modelmentioning
confidence: 99%
“…Refractories [29]: proper drying and outgassing of refractories (and their repairs): converter, ladle, tundish, entry nozzle, submerged tube [25] Gases: purity of oxygen, bottom gas blown in converter, humidity in the air (on top of steel in converter, ladle and tundish) and entrained during exposed pouring operations [27].…”
Section: Hydrogen Sourcesmentioning
confidence: 99%
“…Two strategies have been followed in steel plants to prevent hydrogen problems while controlling processing cost: (a) Evaluating the sources of hydrogen in the steelmaking process (e.g. [6,7,10,[23][24][25]); (b) creating models to estimate the hydrogen content at some step of the melt shop process (e.g. [13,26,27]).…”
Section: Hydrogen Sourcesmentioning
confidence: 99%
“…Liquid steel can pick up hydrogen during steelmaking and casting from refractories, [1] alloys, recarburizers, process gases and additives for slag formation, as hydrogen is strongly soluble. The gravity of such phenomenon also depends on the content of micro-alloying elements, such as manganese.…”
Section: Introductionmentioning
confidence: 99%